Topical prevention from high energy visible light-induced pigmentation by 2-mercaptonicotinoyl glycine, but not by ascorbic acid antioxidant: 2 randomized controlled trials - Piffaut, Virginie; De Dormael, Romain; Belaidi, Jean-Philippe; Bertrand, Laudine; Passeron, Thierry; Bernerd, Françoise; Marionnet, Claire (Frontiers in Pharmacology, 2025)
IntroductionHyperpigmentation and pigmentary disorders are major clinical consequences of sun exposure. While UV radiation is a known contributor, visible light (VL), particularly High Energy Visible (HEV) light (400–450 nm), also induces long-lasting pigmentation in melanocompetent individuals (Fitzpatrick Phototype III and above), and can worsen pigmentary disorders. Therefore, photoprotection in this wavelengths range is recommended to prevent worsening of hyperpigmentation issues. Efficient solutions rely on the use of pigments, absorbing and diffusing VL. However, tint and opacity of these products may limit their use by consumers and patients. The search for actives preventing VL-induced pigmentation is therefore of interest. This work aimed at assessing 2 non tinted biological actives to counteract HEV-induced pigmentation.Material and MethodsTwo very potent inhibitors of UV-induced pigmentation, ascorbic acid 7% (powerful antioxidant) and 2-mercaptonicotinoyl glycine (2-MNG, 0.5 or 1%, melanogenesis inhibitor), were assessed in 2 controlled randomized clinical trials (registered under the identification numbers NCT06945393 and NCT06937515 on ClinicalTrials.gov), including in total, 58 individuals with Fitzpatrick Phototype III or IV. Delineated areas on the subjects back, topically treated or not by the product, were exposed to HEV once a day for 4 days. The product was applied before, during and 5 weeks after HEV exposure. Pigmentation was assessed using chromametry and visual scoring throughout the studies.ResultsWhile ascorbic acid did not exhibit any efficacy versus its vehicle in limiting skin hyperpigmentation induced by HEV, the use of 2-MNG (0.5 or 1%) led to an early significant decrease in HEV-induced pigmentation, which was sustained until the end of the study, as evidenced by colorimetry and significantly scored by visual assessment. Moreover, a 2-MNG dose effect could be evidenced at early time points.Conclusion2-MNG represents an efficient and transparent alternative solution to pigments for the mitigation of HEV worsening of hyperpigmentation issues. This opens up perspectives for its use as a complement to UV protection afforded by sun filters.